Father’s perceptions and care involvement for their very preterm infants at French neonatal intensive care units - Stern-Delfils, Amélie; Leray, Isabelle; Caeymaex, Laurence; Dicky, Odile; Akrich, Madeleine; Reynaud, Audrey; Bouvard, Charlotte; Evrard, Anne; Sizun, Jacques; Tscherning, Charlotte; Kuhn, Pierre; , the GREEN Committee (Groupe de Réflexion et d’Evaluation de l’Environnement des Nouveau-nés de la Société Française de Néonatologie) (Frontiers in Psychiatry, 2023)
Objectives We aimed to evaluate (1) fathers’ perceptions and care involvement for their very premature infants and their views of the hospitalization period based on parental reports and (2) their evolution over time. Methods We used an online parental survey to assess answers from parents of very preterm infants who were successfully discharged from French neonatal units. We analysed answers from February 2014 to January 2019 to an anonymous internet-based survey from the GREEN committee of the French Neonatal Society. Responses were compared for period 1 (P1, 1998 to 2013) and period 2 (P2, 2014 to 2019). Results We analyzed 2,483 surveys, 124 (5%) from fathers and 2,359 (95%) from mothers. At birth, 1,845 (80%) fathers were present in the hospital, but only 879 (38%) were near the mother. The presence of fathers in the NICU increased from P1 to P2 (34.5% vs. 43.1%, p = 0.03). Nearly two thirds of fathers accompanied their infants during transfer to the NICU (1,204 fathers, 60.6%). Fathers and mothers had similar perceptions regarding relationships with caregivers and skin-to-skin contact with their infants. However, more fathers than mothers felt welcome in the NICU and in care involvement regarding requests for their wishes when they met their infant (79% vs. 60%, p = 0.02) and in the presentation of the NICU (91% vs. 76%; p = 0.03). Mothers and fathers significantly differed in the caring procedures they performed (p = 0.01), procedures they did not perform but wanted to perform (p < 0.001), and procedures they did not perform and did not want to perform (p < 0.01). Conclusion Most fathers were present at the births of their very preterm infants, but fewer fathers were near the mother at this time. Less than two thirds of fathers accompanied their infants to the NICU. There should be further changes to better meet the specific needs of the fathers of infants requiring care in the NICU. Continuing assessment with an online questionnaire may be useful to monitor changes over time in father’s involvement in NICUs.